Análise de consignas em material didático para aulas remotas de inglês para crianças em contexto de pandemia - Lima, Lívia de Sousa (2022)
This work is based on the epistemology and methodologies of the Social Discursive Interactionism (SDI), especially on the studies of Bronckart (1999, 2006, 2012) and the debates about language capacities in Dolz, Pasquier, Bronckart (1993) and Dolz (2015), as well as the definitions about instructions developed by Bronckart, Bulea, Fristalon (2004), Riestra (2008) and Zakhartchouck (2016). For this Masters research, we analyzed the instructions set on didactic materials for English teaching for kids in a bilingual program of a private school in Fortaleza in order to foment reflections regarding the appropriateness of the instructions to reach the learning objectives, especially those concerning to the development of language capacities. Some instructions were chosen from the didactic book to evaluate their characteristics and appropriateness for teaching English to 4-year-old children. Using a qualitative approach, the results of this research, which also has an explanatory character, reveals that there are some aspects to improve, especially about the contextualization and specifications beyond the use of verbs in the imperative form. Before the results, we can also affirm that teacher’s mediation is vital in order to fill in the blankets left by the insufficiency in the activity instructions and to modify the practice in the classroom for the children to be able to develop the language capacities.